Mastoid Canals and Grooves in Human Skulls: A Dry Bone Study - UshaVerma; Shavi Garg; Amit Kumar Saxena; Ritu Singroha; Prachi SAneja; Suresh KantaRathee (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: The mastoid canals and mastoid grooves are formed within the mastoid part of temporal bones of skull, these are present on the external surface of mastoid region, anterior to the occipitomastoid suture, behind and parallel to the petrosquamous suture and anteroinferior to the asterion. The study was conducted to observe the incidence of mastoid canals and grooves in dry adult human skulls.Methods: Total of 120 dry adult human skulls consisting of 80 male & 40 female were examined to determine the incidence of mastoid canals and grooves. The mastoid parts of both sides were examined for the presence of mastoid canals and grooves. Then length of mastoid canals was measured.Conclusion: Out of the total of 120 skulls, mastoid canals were observed in 8.75% of skulls. The incidence of mastoid canals was 10% in females and 8.12% in males. The incidence of mastoid grooves was 10.42% of total skulls. It was 11.88 % in male skulls and in female skulls, it was 7.55%. The knowledge of mastoid canals and grooves of the temporal bones is very useful to the neurosurgeons and ENT surgeons while doing surgery to avoid severe bleeding.